الفن والجمال في الفلسفة الغربية ( جون ديوي أنموذجا) - قوقي وئام; ميلودي شروق (جامعة الوادي - University of Eloued, 2025)
تهدف هذه الدراسة إلى تحليل فلسفة الفن والجمال عند جون ديوي وموقعها في سياق تطور الفكر الجمالي الغربي، وذلك من خلال بحث التصورات الفلسفية للجمال من أفلاطون إلى نيتشه، ثم دراسة جوهر الفلسفة البراغماتية التي ينتمي إليها ديوي، وصولاً إلى تحليل مفهوم الخبرة الجمالية عند ديوي ونظريته عن الفن" كخبرة اعتمدت الدراسة على المنهج التحليلي النقدي من خلال تحليل أعمال ديوي خاصة كتابه "الفـن كخبرة" (1934)، والمقارنة مع الفلسفات الجمالية السابقة. توصلت الدراسة إلى أن فلسفة ديوي الجمالية تمثل ثورة في علم الجمال من خلال تجاوز الثنائيات التقليدية وإعادة الفن إلى سياق الحياة اليومية، وإبراز البعد الاجتماعي والتربوي للفن كوسيلة لتعزيز الديمقراطية والنقد الاجتماعي. كما أظهرت الدراسة امتداد أفكار ديوي الجمالية في النظريات المعاصرة وتطبيقاتها في مجال التربية الفنية أوصت الدراسة بضرورة الاهتمام بالبعد التطبيقي للفلسفة الجمالية في الحياة اليومية والمؤسسات التعليمية، وتبني رؤية ديوي في ربط الفن بالخبرة الإنسانية المباشرة لتطوير برامج التربية الفنية وتعزيز الوعي الجمالي في المجتمع. This study aims to analyze John Dewey's philosophy of art and beauty and its position in the context of the development of Western aesthetic thought, by examining philosophical conceptions of beauty from Plato to Nietzsche, then studying the essence of pragmatic philosophy to which Dewey belongs, and analyzing Dewey's concept of aesthetic experience and his theory of "Art as Experience. The study adopted an analytical- critical methodology through analyzing Dewey's works, especially his book "Art as Experience" (1934), and comparing them with previous aesthetic philosophies. The study concluded that Dewey's aesthetic philosophy represents a revolution in aesthetics by transcending traditional dualities and returning art to the context of everyday life, highlighting the social and educational dimension of art as a means to promote democracy and social criticism. The study also showed the extension of Dewey's aesthetic ideas in contemporary theories and their applications in the field of art education. The study recommended the necessity of paying attention to the practical dimension of aesthetic philosophy in everyday life and educational institutions, and adopting Dewey's vision of linking art with direct human experience to develop art education programs and enhance aesthetic awareness in society.
مذكرة ماستر قسم الفلسفة تخصص فلسفة عامة.
Keywords: الفن والديمقراطية; الفن كخبرة; الخبرة الجمالية; البراغماتية; جون ديوي; الفلسفة الجمالية; Aesthetic Philosophy; John Dewey; Pragmatism; Aesthetic Experience; Art as Experience; Art and Democracy.